Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMP Negeri 1 Muara Padang - Teguh Iswanto; Nur Ahyani; Nila Kesumawati (Journal on Education, 2025)
This study aims to describe and analyze the role of principal leadership in improving teacher performance in terms of planning, implementation, and evaluation of teacher performance at SMP Negeri 1 Muara Padang. The method used is a qualitative method. Data collection techniques use observation, interviews and documentation. The results of the study can be concluded that the role of principal leadership in improving teacher performance at SMP Negeri 1 Muara Padang can be divided into 3 stages, namely planning, implementation, and evaluation. The principal's planning to improve teacher performance begins with the formation of a teacher performance assessment team (PK). In its implementation, the team schedules activities, forms of training and details the costs of activities. After the implementation is complete, an evaluation is carried out in the form of supervision. The results of the supervision are formed in a teacher performance assessment report, the results of which have been maximized at SMP Negeri 1 Muara Padang.